DAMPAK PENERAPAN CORETAX PADA PT YEKAPE SURABAYA - Silalahi, Olivia Yunita; Tantina Haryati (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study aims to examine the impact of implementing the Core Tax Administration System (CORETAX) on the effectiveness of tax reporting at PT Yekape Surabaya. CORETAX is an integrated digital tax administration system introduced by the Directorate General of Taxes in early 2025. Using a descriptive qualitative approach, data was collected through semi-structured interviews with two key informants directly involved in the company's tax reporting process. The findings indicate that CORETAX positively affects tax reporting efficiency, system integration, and data transparency. All types of taxes can now be reported through a single platform, replacing the previous manual and segmented applications. However, challenges remain, particularly related to human resource adaptation, system navigation, and technical disruptions during the initial phase. PT Yekape addressed these challenges through internal training and interdepartmental coordination. The study concludes that the success of CORETAX implementation heavily depends on organizational readiness—both technical and human—and the strategic role of internal leadership in supporting the digital transition.